Efficient Screening of Bi–Metallic Electrocatalysts for Glycerol Valorization. (1st December 2021) - dos Santos, Egon Campos; Araujo, Rafael B.; Valter, Mikael; Salazar-Alvarez, German; Johnsson, Mats; Bajdich, Michal; Abild-Pedersen, Frank; Pettersson, Lars Gunnar Moody
Highlights: Biodiesel Industry. Glycerol Valorization. Bi-metallic electrodes. Abstract: Glycerol is a byproduct of biodiesel production and, as such, it is of limited economic value. By means of electrooxidation, glycerol can be used as a feedstock for scalable hydrogen production, in addition to conversion to value-added products. The development of novel and efficient catalytic electrode materials for the anodic side of the reaction is a key towards a hydrogen-based energy economy. In the present study, a computational screening protocol combining DFT, scaling relations, and microkinetic modeling allows for a rational selection of novel catalysts that can deliver efficient glycerol electrooxidation, low cost of production, and environmental sustainability. Activity and chemical selectivity towards hydrogen production on pure metal catalysts is discussed in terms of volcano-shaped plots. We find that the selectivity in the glycerol oxidation reaction is influenced by a different energy landscape when in the presence of water and best classified by a comparison of OH and CH bond-breaking barriers. In addition, we screened 3570 bi-metallic catalysts in the AB (L10 ) and A3 B (L12 ) ordered structures for activity, stability, price, and toxicity. By filtering based on the criteria for toxicity, resistance to oxidation, miscibility, and price, we have identified 5 L10 structured catalysts (AgPd, AuPd, PtSb, CuPt, and AgPt) and 20 L12 catalysts (Ga3 Ta, In3 Ta, Ir3 W, Ir3 Mo, Cu3 Pt, Ir3 Ta, Ir3 Re, Pd3 Bi, Pd3 Cu, Pd3 W, Pd3 Co, Pd3 Sn, Pd3 Mo, Pd3 Ag, Pd3 Ga, Pd3 Ta, Au3 Ru, Pd3 In, Au3 Ir, and Pd3 Au) that are all predicted to show high activity. We also identify an additional 37 L10 and 92 L12 structured electrocatalysts with an anticipated medium-high activity. Graphical_Abstract: Image, graphical abstract